2018
DOI: 10.1111/ger.12368
|View full text |Cite
|
Sign up to set email alerts
|

Oral health and dental care of older persons—A systematic map of systematic reviews

Abstract: There is an urgent need for further research and evidence-based knowledge within most domains in geriatric dentistry and in other fields related to oral health and dental care for older persons striving for multi-disciplinary research programmes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
85
0
6

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 89 publications
(92 citation statements)
references
References 60 publications
1
85
0
6
Order By: Relevance
“…Regarding oral health, the increasing number of elderly people who retain their natural teeth presents a challenge in preventive and restorative dental care [10]. Continuous collection of data such as those from national oral health surveys are able to illustrate oral health development with a significant increase in relevant data pertaining to the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding oral health, the increasing number of elderly people who retain their natural teeth presents a challenge in preventive and restorative dental care [10]. Continuous collection of data such as those from national oral health surveys are able to illustrate oral health development with a significant increase in relevant data pertaining to the elderly population.…”
Section: Introductionmentioning
confidence: 99%
“…Caregivers might therefore perceive a conflict between respecting a patient's autonomy and the provision of good care. Furthermore, as a patient's general health worsens, less importance is often placed on their dental health [4,13].…”
Section: Introductionmentioning
confidence: 99%
“…A 2006 systematic review revealed that temporomandibular disorder, poor oral health, dissatisfaction with teeth and mouth, and oral dryness diminished oral health-related quality of life, which was low among people without teeth 13) .…”
Section: Introductionmentioning
confidence: 99%